Comparative Efficacy Of Some Insecticides Under Laboratory Conditions Against 5th Instar Larva Of Swallowtail Butterfly, Papilio Demoleus (Linn.) (Applied Biological Research, 2023)
The swallowtail butterfly, Papilio demoleus (L.), is a serious insect-pest that  causes huge losses to citrus crop. The caterpillars of P. demoleus are voracious  feeder of citrus leaves. In order to control caterpillars, the lethal dose (LD50)  and relative toxicity of three groups of insecticides i.e. synthetic pyrethroids  (deltamethrin, cypermethrin and fenvelerate), organochlorine (endosulfan)  and organophosphate (monocrotophos, phosphomidon and quinalphos) were  estimated against 5th instar larva of P. demoleus. The LD50 values were worked  out by topical method using acetone as solvent. The synthetic pyrethroids gave  much lower LD50 values as compared to the organophosphate and organo chlorine insecticides. Deltamethrin proved most toxic insecticide against 5th instar larvae of P. demoleus showing the LD50 of deltamethrin, cypermethrin,  fenvalerate, endosulfan, quinalphos, monocrotophos, and phosphamidon as  0.00753836, 0.0098852, 0.021728, 0.179888, 0.3027134, 0.997872, and 2.518973 µg g-1, respectively. The relative toxicity of test insecticides against 5th instar  larvae was in descending order as deltamethrin > cypermethrin > fenvalerate  > endosulfan > quinalphos > monocrotophos > phosphomidon.
Keywords: Infestation; insecticides; larvae; voracious feeder; relative toxicity